Effect of weight loss on the course of non-alcoholic fatty liver disease: results of 6-month follow-up - L. V. Chesnokova; I. M. Petrov; I. A. Troshina; M. V. Goncharova; I. V. Medvedeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2015)
Aim of investigation. To study the effect of nonpharmaceutical correction of body weight on the level ofhigh cardio-vascular risk markers at non-alcoholic fatty liver disease (NAFLD).Material and methods. Overall 117 patients with NAFLD at steatosis stage combined to obesity or metabolic syndrome (MS) — 59 and 58 patents respectively, mean age 43 years (38 to 46 years) and 45 years (39- 49) were investigated. Levels of lipid and carbohydrate metabolism markers, TNF-α, leptin, adiponectin and nitric oxide (NO) metabolites were evaluated.Results. Weight loss for at least 5% was gained in 44,1% of patients with NAFLD in association to obesityand in 56,6% of those with NAFLD in combination to MS, that was accompanied by significant reduction of lipid atherogenic fraction levels (cholesterol, low density lipoproteins), decrease of insulin resistance index, CRP and TNF-α inflammation markers, and decrease of leptin concentration in MS group. Comparative analysis of adiponectin and NO metabolites concentration has shown demonstrated, that in patients with NAFLD both in combination to obesity, and in combination to MS the target level of weight loss is accompanied by elevation of adiponectin level (р<0,05) and NO stable metabolites (р<0,05), whereas concentration of nitrites is increased significantly (р<0,05) only in obese patients.Conclusions. Weight loss for 5% and over at steatosis stage of NAFLD is characterized by decrease ofbiochemical cardio-vascular risk markers, in addition the group with 40 min/day physical exercises inefficacy had lower level of insulin resistance index and TNF-α along with higher levels of NO metabolites.